2014
DOI: 10.1001/jamaneurol.2013.6240
|View full text |Cite
|
Sign up to set email alerts
|

Switching From Natalizumab to Fingolimod in Multiple Sclerosis

Abstract: IMPORTANCE The safety and efficacy of switching from natalizumab to fingolimod have not yet been evaluated in a large cohort of patients with multiple sclerosis (MS) to our knowledge.OBJECTIVE To collect data from patients with MS switching from natalizumab to fingolimod. DESIGN, SETTING, AND PARTICIPANTSThe Enquête Nationale sur l'Introduction du Fingolimod en Relais au Natalizumab (ENIGM) study, a survey-based, observational multicenter cohort study among MS tertiary referral centers. Participants were pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
116
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(129 citation statements)
references
References 14 publications
10
116
0
Order By: Relevance
“…However, there is no established guideline on an appropriate washout period between NTZ and FTY. A study in a French prospective cohort recommended a washout period shorter than 3 months,86 whereas a large prospective international registry advised a maximum 2‐month treatment gap for switches to FTY to reduce the risk of relapse 87. These studies suggest that a prolonged washout period might do more harm than good, and washout should be no longer than 2 months.…”
Section: Fingolimod and Progressive Multifocal Leukoencephalopathy‐rementioning
confidence: 99%
“…However, there is no established guideline on an appropriate washout period between NTZ and FTY. A study in a French prospective cohort recommended a washout period shorter than 3 months,86 whereas a large prospective international registry advised a maximum 2‐month treatment gap for switches to FTY to reduce the risk of relapse 87. These studies suggest that a prolonged washout period might do more harm than good, and washout should be no longer than 2 months.…”
Section: Fingolimod and Progressive Multifocal Leukoencephalopathy‐rementioning
confidence: 99%
“…Results from the ENIGM study [9] in 333 patients switching from natalizumab to fingolimod (69.1% patients underwent a 6-month follow up) highlighted the importance of a natalizumab washout duration of less than 3 months, as these patients had a significantly lower risk of relapse than those who underwent a longer washout period. Despite having a similar proportion of relapsing patients, in subgroup with the same washout length, we did not find a relationship between the washout length and the relapse rate, perhaps due to the small number of patients in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Fingolimod (Gilenya, Novartis, Basel, Switzerland) is an option for these patients [1,3,[8][9][10][11][12] however, because of the still unknown impact on the immune system of the concomitant presence of these molecules, an interval is recommended between discontinuing natalizumab and starting fingolimod. Studies investigating switching from natalizumab to fingolimod have shown clinically relevant disease activity during the first weeks of fingolimod treatment, challenging its effectiveness in this setting, and highlighting the need to clarify its role in patients with a disease characterized by its severity and rapid evolution, and to improve the switching protocol [9,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The obvious candidate in this situation appears to be fingolimod which was recently shown to be advantageous over injectables after cessation of natalizumab [98], but is probably clinically less potent than natalizumab. Furthermore, some recent data strongly suggest that a switch from natalizumab to fingolimod may be associated with an increased risk of developing new disease activity [99,100]. A recent report came to the conclusion that too-long washout phases between natalizumab discontinuation and fingolimod initiation may elevate that risk and recommends waiting 4-8 weeks between treatments [101].…”
Section: Switching Between Second-line Therapiesmentioning
confidence: 99%